MALAYSIA'S ECONOMIC TRANSFORMATION: EVALUATING INCOME INEQUALITY THROUGH THE LENS OF ETHNIC KNOWLEDGE AND ATTITUDES - Lawson, Roslan Fuyuki (Top Journal of Public Policy and Administration (TJPPA), 2023)
Income inequality among Malaysia's major ethnicities, namely the Malay (Bumiputera), Chinese, and Indian communities, has persisted as a pressing issue since the end of colonial rule. Colonial policies left a legacy of high inequality and poverty rates, largely affecting the Malay majority and fostering an enduring urban-rural divide. The introduction of the Preferential Bumiputera Policy in 1971 aimed to uplift the ethnic Malays but inadvertently led to significant emigration of non-Bumiputera citizens due to education and employment restrictions imposed by the policy. This policy, focusing on Bumiputera share ownership and mandatory employment quotas, lasted for two decades, and its repercussions are still felt today. Within Malaysia, ethnic discrimination is notably prevalent in business communities and the middle class. For instance, Malay partners may secure rents to gain access to government-determined business opportunities, while ethnic Chinese partners, with access to capital and business acumen, excel in execution. This dynamic has been highlighted in various studies (Jomo, 2004). Research by Khalid and Yang (2019) indicates varying growth rates among the ethnic groups, with Bumiputera experiencing the highest real income per adult growth at 8.3%, followed by Indians at 3.4%, and Chinese at -0.6%. These disparities have fueled resentment among the ethnic communities and led to a significant outflow of Chinese Malaysians abroad, resulting in a shortage of highly skilled labor in Malaysia. This paper seeks to provide a comprehensive analysis of income inequality among Malaysia's major ethnicities, tracing its historical roots, and examining the enduring impact of the Preferential Bumiputera Policy. By exploring the dynamics of ethnic discrimination in business and the consequences of varying growth rates, this research contributes to a deeper understanding of Malaysia's complex socio-economic landscape